LEARNING FUNCTION WITH ONLINE TRANSPORT APPLICATION - Lestari, S R; Hartono, Yusuf; Somakim, Somakim (Sriwijaya University Learning and Education International Conference, 2018)
Function is one of subject of math in the high school student. Transportation online is one of the most popular application in Indonesia. We present activities using calculate the cost in online transportation. This study aims to produce a learning trajectory of using online transportation. Therefore, the design research was chosen to meet the research aims and to give in formulating and developing local instructional theory in learning function. Learning trajectory designed in the early phases and tested on 6 eight-grade students in the public islamic junior high school number 2 Palembang (MTsN 2 Model Palembang). The results showed that the activity of using online transportation can stimulate informal knowledge of students in the selection of objects where order does not matter. Furthermore, activities of using online transportation can be used by students gradually developed into more formal mathematics.